Calculated Radioactivity Yields of Gallium-67 using Matlab Codes - Imam Kambali (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2019)
In nuclear medicine, gallium-67 (67Ga) is potentially applied for imaging a certain type of tissue. In this investigation, 67Ga is theoretically studied in terms of its potential radioactivity yields at the end of various energetic proton bombardments. Nuclear cross-sections derived from the Talys Evaluated Nuclear Data Library (TENDL) 2017 were used as the input files, while a Matlab code was developed to perform the yield calculations of 67Zn(p,n)67Ga and 68Zn(p,2n)67Ga nuclear reactions to produce 67Ga. Two different targets – enriched 67Zn and natZn targets – were simulated in the calculations. The calculated yields suggested that a maximum of 27.37 MBq/µAh could be achieved when enriched 67Zn target was irradiated with 15-MeV protons, whereas 46.99 MBq/µAh could be generated following a 30 MeV proton bombardment of enriched 68Zn target. Various radioactive gallium impurities, i.e. 63,64,65,66,68,70Ga and stable 69Ga isotope were also expected to be generated mostly via (p,n) and (p,2n) reactions when natZn target was used in the 67Ga production. In contrast, radioactive 66Ga and 68Ga impurities were mainly produced following bombardment of enriched 67Zn and 68Zn targets. This study can be used as a reference for future 67Ga radionuclide production.